Promoting effects of 6-Gingerol on probiotic adhesion to colonic epithelial cells - JIANG,Qian (2021)
Abstract The effects of 6-gingerol on adhesive ability of probiotics to colonic epithelial cells in vitro were explored. Two strains of probiotics were Lactophilus acidophilus and Bifidobacterium bifidum. NCM 460 cells (normal colonic epithelial cells) and Caco-2 cells (colon cancer cells) were used in this study. Effect of 6-gingerol (5, 10, 15, 20, 25, 30, 35, 40 μg/mL on NCM 460 cells and effect of 6-gingerol (10, 25, 50, 75, 100, 125, 150, 175 μg/mL) on Caco-2 cells were investigated. MTT assay was adopted to analyze cell proliferation. Methods of Gram staining and plate counting were used to analyze the probiotic adhesion to colonic epithelial cells. Results showed that 6-gingerol had no inhibitory effect on colonic epithelial cells within the non-cytotoxic dose range. 6-gingerol could promote the adhesion of probiotics to colon epithelial cells in a dose-dependent manner, which would be benefit for probiotics to exert continuous probiotic activity in the intestinal tract.